2018
DOI: 10.1097/01.ogx.0000542484.75708.ba
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Fetal Alcohol Spectrum Disorders in 4 US Communities

Abstract: (Abstracted from JAMA 2018;319(5):474–482) Several single-site, active-case ascertainment studies in the United States have shown widely varying prevalence estimates for fetal alcohol spectrum disorders, composed of fetal alcohol syndrome, partial fetal alcohol syndrome, and alcohol-related neurodevelopmental disorder. Prevalence of fetal alcohol spectrum disorders are challenging to estimate using routine surveillance methods, and cases are often misdiagnosed or undiagnosed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
221
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 148 publications
(222 citation statements)
references
References 0 publications
1
221
0
Order By: Relevance
“…Global FAS prevalence estimate intervals range from 0 to 176.77 per 1,000 live births (Roozen et al, 2016). Data by May and Chambers, 2018, that lead to a conservative prevalence of FASD in 4 communities in the United States of 1.1 to 5% of school-age children are certainly alarming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global FAS prevalence estimate intervals range from 0 to 176.77 per 1,000 live births (Roozen et al, 2016). Data by May and Chambers, 2018, that lead to a conservative prevalence of FASD in 4 communities in the United States of 1.1 to 5% of school-age children are certainly alarming.…”
Section: Discussionmentioning
confidence: 99%
“…b Fetal alcohol syndrome (May and Gossage, 2001). c Fetal alcohol spectrum disorders (May et al, 2018). We excluded estimates for FASD in live births and preschool categories, since ARND is diagnosed only from the school age.…”
Section: Discussionmentioning
confidence: 99%
“…A very recent prevalence study in the general US population provided a conservative estimate of 11.3-50 per 1000 children. 16 The prevalence rate of FASD amongst the general population in Australia is currently unknown. An Australian study in a selected high-risk population reported some of the highest rates of FASD in the world (i.e.…”
Section: Prevalencementioning
confidence: 99%
“…23 In the interim, the focus Table 3 Selection of quotes from Queensland Fetal Alcohol Spectrum Disorder (FASD) Support Group, following a Facebook-posted question -What they would like to tell their paediatrician? (May, 2018) • 'A parent knows when there is something wrong with our children so listen' • 'We come to professionals hoping you know more than us' • 'Don't be afraid to ask the mum if alcohol could have been consumed in the pregnancy. But don't do it accusingly and don't judge the mother by making her feel guilty or blaming and shaming her' • 'You don't have to be an alcoholic to have a child with FASD.…”
Section: Future Considerationsmentioning
confidence: 99%
“…The latest study from the USA gives a conservative estimate of 1.1% to 5% among 7-year-old children, and a less conservative approach gives an estimate of 3% to 10%. 5 As a reminder, the prevalence of CP is around 0.2%. Both CP and FASD are lifelong disorders of varying severity.…”
mentioning
confidence: 99%